2011
DOI: 10.1590/s1413-35552011005000027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of equine-assisted therapy on the postural balance of the elderly

Abstract: Objective: To determine whether equine-assisted therapy (hippotherapy) produces alterations in the balance of the elderly. Methods:The sample included 17 older adults who were divided into experimental (7 subjects) and control (10 subjects) groups. Stabilometry data were acquired with a force platform. The Timed Up and Go test (TUG) was used for clinical analysis of seated balance, transfer from a seated to a standing position, walking stability and changes in gait. Sixteen equine-assisted therapy sessions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 19 publications
2
35
0
6
Order By: Relevance
“…In this study, the length of postural sway in standing with the eyes open and closed significantly decreased after 8 weeks of exercise. However, Araujo observed that the static balance of the elderly who live at home didn’t show significant difference after horse riding exercise9 ) . The differences between the findings of this study and previous reports may be due to the health status of the subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the length of postural sway in standing with the eyes open and closed significantly decreased after 8 weeks of exercise. However, Araujo observed that the static balance of the elderly who live at home didn’t show significant difference after horse riding exercise9 ) . The differences between the findings of this study and previous reports may be due to the health status of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Mitani used a device similar to the HRS in our present study, and the study of Araujo. Which conducted equine-assisted therapy, showed that elderly individuals had shorter TUG performance time and increased gait speeds after horse riding exercise9, 17 ) . In our present study, the HRS group demonstrated better dynamic balance ability and gait ability than those of the ball exercise group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially looking for food and materials for making clothes and tools, the primitive man had also found an ally that would provide relatively fast transport, and later an important instrument of war, agriculture, and trade. Still later, this partnership would inaugurate a new concept in supportive therapy for people with special needs, limited physical abilities [2,3], and scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of using horses to improve the health of individuals (healing) mean that a physical, psychological or social improvement has occurred. Specific consequences include improved postural balance, mental well‐being, and quality of life; trust is conveyed; spasticity is decreased; pleasure is increased by stroking, grooming, and warmth; and improved neurological pathways (Araujo, Silva, Costa, Pereira, & Safons, ; Beinotti et al, ; Borioni et al, ). Small studies have shown increased self‐efficacy, self‐esteem and nurse presence (concentrating on the patient's needs) (Hessel, ), and improved mood and a sense of accomplishment (DeZutti, ; Walsh & Blakeney, ).…”
Section: Resultsmentioning
confidence: 99%